Iterative Development of a Serious Game for Older Adults: The Usability-Informed Approach - Yampray, Karuna; Choemprayong, Songphan; Taiphapoon, Tatri (Journal of Advanced Development in Engineering and Science, 2026)
This study presents the iterative usability evaluation of The Happy Cruise, a serious game specifically developed for older adults to support lifestyle-based market segmentation. Older adults represent a distinct user group facing usability challenges such as physical limitations, cognitive decline, and reduced digital engagement. To address these issues, the research adopted a problem–solution approach that integrated Nielsen’s Usability Heuristics, Task Analysis, and the Serious Game Design Assessment (SGDA) Framework within an iterative design cycle. Twelve participants aged 60–75 completed expert reviews, task performance assessments, and user interviews. In the first iteration, eight participants experienced difficulties with navigation and input mechanisms. After implementing design modifications informed by heuristic evaluation and participant feedback, satisfaction improved substantially, with ten reporting positive experiences in the final iteration. While ensuring data collection for market segmentation, findings highlight the importance of intuitive interfaces, adaptable difficulty levels, engaginggameplay, and social interaction features in developinginclusive gaming experiences for older adults. The study’s novelty lies in demonstrating the rigorous integration of Nielsen’s Heuristics, Task Analysis, and the SGDA Framework for designing serious games tailored to older adults.